Chapter «... Ricondurre in qualche modo il buon ordine e impedire nuovi scandali». La visita apostolica ai monasteri olivetani toscani del 1843 - Giovannoni, Pietro Domenico (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
Between 1843 and 1845 Pope Gregory XVI entrusted the two Tuscan Olivetan monasteries, Monte Oliveto Maggiore in the Sienese area and San Bartolomeo in Florence, to the jurisdiction of the Archbishop of Florence Ferdinando Minucci with the task of conducting an apostolical visit. At the same time, the Tuscan government, following the legislation of Pietro Leopoldo, instructed the Archbishop himself to conduct a visit to the same monasteries in the name and on behalf of the State. The essay analyses the story by cross-examining the ecclesiastical sources with those of the Government. An episode emerges that testifies to the persistence of dynamics typical of the ancient regime regarding the relations between State and Church in the context of the Restoration age.